H2O2-Responsive Hormonal Status Involves Oxidative Burst Signaling and Proline Metabolism in Rapeseed Leaves - Bok-Rye Lee; Van Hien La; Sang-Hyun Park; Md Al Mamun; Dong-Won Bae; Tae-Hwan Kim (MDPI AG, 2022)
Drought alters the level of endogenous reactive oxygen species (ROS) and hormonal status, which are both involved in the regulation of stress responses. To investigate the interplay between ROS and hormones in proline metabolism, rapeseed (Brassica napus L.) plants were exposed to drought or exogenous H2O2 (Exo-H2O2) treatment for 10 days. During the first 5 days, the enhanced H2O2 concentrations in drought treatment were associated with the activation of superoxide dismutase (SOD) and NADPH oxidase, with enhanced ABA and SA levels, while that in Exo-H2O2 treatment was mainly associated with SA-responsive POX. During the latter 5 days, ABA-dependent ROS accumulation was predominant with an upregulated oxidative signal-inducible gene (OXI1) and MAPK6, leading to the activation of ABA synthesis and the signaling genes (NCED3 and MYC2). During the first 5 days, the enhanced levels of P5C and proline were concomitant with SA-dependent NDR1-mediated signaling in both drought and Exo-H2O2 treatments. In the latter 5 days of drought treatment, a distinct enhancement in P5CR and ProDH expression led to higher proline accumulation compared to Exo-H2O2 treatment. These results indicate that SA-mediated P5C synthesis is highly activated under lower endogenous H2O2 levels, and ABA-mediated OXI1-dependent proline accumulation mainly occurs with an increasing ROS level, leading to ProDH activation as a hypersensitive response to ROS and proline overproduction under severe stress.